The educational space and its impact on pedagogical dynamics: Teachers’ perception of their working environment - Poyato-Nunez, Marta Maria; Olmos-Gomez, Maria del Carmen; Parra-Gonzalez, Maria Elena (Journal of Education and e-Learning Research, 2024)
A quality learning space provides students with an optimal environment for social relations, collaborative work and participation, thus fostering innovation and incorporating active methodologies. The aim of this study is to analyze whether the design of existing learning environments is suitable for incorporating innovation in classrooms. The methodology carried out in this study was quantitative and divided into two phases to carry out the analysis. The approach consisted of collecting data from a sample of 245 teachers using a questionnaire designed and validated by the researchers. The teachers perform their educational activity between the 3rd and 6th grades of primary school and are in educational centres in the autonomous city of Ceuta (Spain). The findings highlight the relevance that teachers believe the design of educational spaces should have in the teaching-learning process. Thus, the results show that there are significant differences with respect to age and professional experience in relation to the teacher’s perception of infrastructure. Therefore, it is important to conclude by highlighting the consideration of the educational space as an essential element for the incorporation of methodological renewal in the classroom.